COMPONENTS OF METABOLIC SYNDROME AS A RISK FACTOR FOR COVID-19 IN INDIA - GUNJAN KUMAR MANDAL (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Several patients with components of metabolic syndrome (MetS) like obesity, hypertension, diabetes mellitus and dyslipidemia is a risk factor for COVID-19 in India. Aims of our review to bring together current data about components of metabolic syndrome & COVID 19 infection. It specially looks the relation between components of MetS (Obesity, Diabetes mellitus, Hypertension and dyslipidemia) and COVID 19. At the time of writing the review is updated till time. Methods: Search of literature was done by using google search & PubMed engines for prepare review related to my article. Results: Patients with components of metabolic syndrome like obesity, diabetes, hypertension and dyslipidemia have increased evidence of incidence and severity of COVID-19. COVID-19 has effect on the pathophysiology of all these components of metabolic syndrome. The control of all these components of metabolic syndrome is important not only for patients who are infected with COVID-19, but also for those without the disease. Conclusions: It is commonly known that the existence of comorbidities such as increase in BMI, dyslipidemia, diabetes mellitus and hypertension is associated with additional severe course of COVID-19. So measurement of components of metabolic syndrome parameters is essential to better estimate the risk of COVID-19 and management and control of these components (BMI, blood glucose, blood pressure, lipid profile) of metabolic syndrome parameters will cause less possibility to occur COVID-19.